Graptocarcininae n. subfam., an extinct subfamily of Dynomenidae Ortmann, 1892 (Crustacea, Brachyura, Podotremata) - van Bakel, Barry W. M.; Guinot, Danièle; Corral, José Carmelo; Artal, Pedro (Zootaxa, 2012)
Newly available material of a dynomenid crab, Graptocarcinus urbasaensis n. sp., from the Upper Cretaceous of northernSpain (Álava and Navarra), allowed the study of the morphology of well preserved ventral surfaces. We describe a newsubfamily of Dynomenidae, comprising the middle-Upper Cretaceous Graptocarcinus and the Upper Jurassic Cyclothy-reus. Graptocarcininae n. subfam. shows a primitive configuration of the abdomen and an abdominal holding mechanismthat is similar to that of the Acanthodromiinae. Recognition of this ancient extinct subfamily confirms that the Dynomenidae is amongst the most basal brachyuran families.